Membangun Komunikasi Suami-Istri Sebagai Sarana Keharmonisan Keluarga - Juanda Juanda; Sjanette Eveline (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2018)
The smallest organization in the world is family. Beginning with husband and wife and so on developing into a family. When building a harmonious family often experience obstacles. In fact, any obstacle if you want to be investigated will come from the failure to establish husband and wife communication. Even though this is very important to avoid the division between the husband and wife. Indeed, here requires its own struggle. There needs to be awareness and willingness to learn to communicate with their partners. This is the result of the couple's maturity.